THE IMPORTANCE OF UNCONTROLLED AND INFRINGING PREVENTION AMONG YOUNG PEOPLE IN THE EDUCATIONAL PROCESS - Astanakulov Kamalitdin Makhkamovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article tells about the future of society, how the younger generation is brought up and brought up, that the idea of creation and destruction is the idea of our ideology, as well as how, on the basis of a conversation, the child opens up the inner world and creates an opportunity to have a positive impact on his mental state opinion analysis.